Online banking adoption: an empirical analysis - Chong, Alain Yee Loong; Ooi, Keng Boon; Lin, Binshan; Tan, Boon In (Emerald Publishing Limited, 2010)
Purpose – This paper aims to empirically examine the factors that affect the adoption of online banking in Vietnam. Perceived usefulness, perceived ease of use, trust and government support were examined to determine if these factors are affecting online banking adoption.